Gradually Increasing Tidal Volume May Mitigate Experimental Lung Injury in Rats. (May 2019) - Felix, Nathane S.; Samary, Cynthia S.; Cruz, Fernanda F.; Rocha, Nazareth N.; Fernandes, Marcos V. S.; Machado, Joana A.; Bose-Madureira, Rebecca L.; Capelozzi, Vera L.; Pelosi, Paolo; Silva, Pedro L.; Marini, John J.; Rocco, Patricia R. M.
Editor's Perspective: What We Already Know about This Topic: High tidal volumes and pressures may worsen acute lung injury, sometimes resulting in a trade-off between inflicted damage versus inadequate ventilation What This Article Tells Us That Is New: In a rat model of experimental lung injury, gradually increasing tidal volume to a known injurious level may result in less (or in some circumstances, more) damage Background: This study hypothesized that, in experimental mild acute respiratory distress syndrome, lung damage caused by high tidal volume (VT ) could be attenuated if VT increased slowly enough to progressively reduce mechanical heterogeneity and to allow the epithelial and endothelial cells, as well as the extracellular matrix of the lung to adapt. For this purpose, different strategies of approaching maximal VT were tested. Methods: Sixty-four Wistar rats received Escherichia coli lipopolysaccharide intratracheally. After 24 h, animals were randomly assigned to receive mechanical ventilation with VT = 6 ml/kg for 2 h (control); VT = 6 ml/kg during hour 1 followed by an abrupt increase to VT = 22 ml/kg during hour 2 (no adaptation time); VT = 6 ml/kg during the first 30 min followed by a gradual VT increase up to 22 ml/kg for 30 min, then constant VT = 22 ml/kg during hour 2 (shorter adaptation time); and a more gradual VT increase, from 6 to 22 ml/kg during hour 1 followed by VT = 22 ml/kg during hour 2 (longer adaptation time). All animals were ventilated with positive end-expiratory pressure of 3 cm H2 O. Nonventilated animals were used for molecular biology analysis. Results: At 2 h, diffuse alveolar damage score and heterogeneity index were greater in the longer adaptation time group than in the control and shorter adaptation time animals. Gene expression of interleukin-6 favored the shorter (median [interquartile range], 12.4 [9.1–17.8]) adaptation time compared with longer (76.7 [20.8 to 95.4]; P = 0.02) and no adaptation (65.5 [18.1 to 129.4]) time ( P = 0.02) strategies. Amphiregulin, metalloproteinase-9, club cell secretory protein-16, and syndecan showed similar behavior. Conclusions: In experimental mild acute respiratory distress syndrome, lung damage in the shorter adaptation time group compared with the no adaptation time group was attenuated in a time-dependent fashion by preemptive adaptation of the alveolar epithelial cells and extracellular matrix. Extending the adaptation period increased cumulative power and did not prevent lung damage, because it may have exposed animals to injurious strain earlier and for a longer time, thereby negating any adaptive benefit. Abstract : In a rat model of experimental lung injury, gradually increasing tidal volume to a known injurious level may result in less (or in some circumstances, more) damage.Supplemental Digital Content is available in the text.